Study of bioactivity of complexed DNA in biodegradable polymer films - Debasish Mondal (2010)
Sustained DNA delivery from polymeric films provides a means for enhanced and prolonged gene therapy. However, in the case of bioactive molecules such as pDNA, there are limitations on the achievable release profiles as well as on the maintenance of bioactivity over time. To address these issues, in this research project various polymeric formulations were developed in which DNA was incorporated. The polymeric system consists of a biodegradable semi crystalline polymer such as PCL blended with a hydrophilic polymer such as gelatin, hyaluronic acid (HA), PEG, PVP, or the sodium salt of poly acrylic acid (PAA). Release studies of pDNA and complexed DNA from different polymeric films were performed by quantifying the amount of DNA released at specific time points over a period of month, utilizing the fluorescence of ethidium bromide complexed to DNA. The studies show that the release of pDNA and complexed DNA from polymer film can be sustained for several days. In all the cases studied, a rapid initial in vitro release was obtained for pDNA, while the release of the complexed pDNA was slower, and sustained for a month. To rationalize the observed release profiles, polymeric films were characterized by SEC, SEM, pore size measurement and confocal fluorescence microscopy.